The Concept of Civil Rights - Freve, Dorian A. (My University, 1971)
This thesis is an attempt to look at the concept of civil rights. Usually civil rights have been acknowledged as those rights which are legally extended to the citizen. Recently though, the term has taken on a meaning similar to that of natural rights. I have, therefore, looked at the meaning of natural rights, decided that natural rights reduced themselves to being moral rights and then found that moral rights are an expression of emotion. I was then able to argue that all rights are civil rights, i.e., rights extended to the citizen by the government. It was necessary to look at the social contract which I accepted as valid. I found it to be the means through which the government was established and the instrument through which certain civil rights are guaranteed.
Keywords: Philosophy; Philosophy